Psychosocial risk factors in development of low back pain in nurses working in intensive care unit of Clinical center of Montenegro - Dragana Jovanović; Dragana Backović; Ljubica Pejakov (Биомедицинска истраживања, 2020)
Introduction: Low back pain is common in adult population, especially in nurses working in the intensive care units. In our country, the subject has not been investigated so far. The aim of the paper is to examine the frequency of low back pain and its connection to psychosocial characteristics. Methods: The questionnaire consisting of general demographic data, questions concerning low back pain, the Beck Inventory of Depression, as well as of the Quebec Back Pain Disability Scale, was created. The sample consisted of 50 nurses working in different areas of intensive care unit in the Clinical Center of Montenegro. Results: The incidence of low back pain (82%) was in accordance with the data collected all around the world, while the incidence of severe low back pain was significantly higher (46%). There was a statistically significant correlation between low back pain measured by the Quebec Back Pain Disability Scale and age and length of service in the intensive care unit. The average results on the Quebec Back Pain Disability Scale were significantly higher in respondents aged ?40 years compared with the younger groups. Nurses whose length of service was ?20 years had higher scores on the Quebec Back Pain Disability Scale than those whose length of service was ? 5 years. There was also a significant correlation between the score on the Quebec Back Pain Disability Scale and the Beck Inventory of Depression (0.44). Conclusion: It was considered that the lack of medical equipment in the intensive care units was one of the causes of low back pain. Furthermore, insufficient amount of knowledge concerning the importance of protective position use while working with patients reduced their use, which in turn influenced the incidence and severity of low back pain. These two factors had cumulative effect and were observed more frequently in the older respondents, i.e. in those nurses whose length of service was ?20 years.
Keywords: low back pain; intensive care unit; nurses; depression; Montenegro